Behaviour of Hybrid Fibers in Oil Palm Shell and Palm Oil Fuel Ash Reinforced Concrete Beam - Sharifah Maszura, Syed Mohsin; M. S., Zainal; Jokhio, Gul A.; Khairunisa, Muthusamy (Centre for Advanced Research on Energy (CARe), 2017)
The paper presents the invescotigatton of structural behavior of hybrid fibers in oil palm shell (OPS)and palm oil fuel ash (POFA) rcinforced concrete beam. Four-point bending test was conducted on five beams with various fiber volume fraction ranging from 0 % to 2.0 %. Based on the results obtained, it was observed that fibers have the capability to increase the load carrying capacity, shear strength and ductility of the beam. Moreover, the crack propagation is lower when the amount of fiber is increased.